ENGLISH FOR COMPUTER SCIENCE : SEBUAH ANALISIS KEBUTUHAN BAHASA INGGRIS PADA MAHASISWA TEKNIK INFORMATIKA - Puspitasari, Indah (STMIK Amiko Purwokerto, 2013)
This research refers to qualitative, so the results and discussion that discussed in the form of descriptive and interpretative based on relevant theories . This study aimed to describe the problems faced by students in learning English , analyzes the needs of English for Information Technology Student and interpret it in the framework syllabus . There are several steps that the author did . The first step was library study method. It was to collect , observe and analyze relevant theories to make the research instruments (questionnaires). The second step was to share research instruments (questionnaires) distributed to students in Computer Science 2013 STMIK Amikom Purwokerto , University General Soedirman (UNSOED) and the University Muhammadiah Purwokerto (UMP) . The third step was to nalysis results of the questionnaire . The analysis included the analysis of the problems and needs of English at the Computer Science students (English for Computer Science)